The epilepsy phenotypic spectrum associated with a recurrent CUX2 variant. Issue 5 (30th April 2018) - Chatron, Nicolas; Møller, Rikke S.; Champaigne, Neena L.; Schneider, Amy L.; Kuechler, Alma; Labalme, Audrey; Simonet, Thomas; Baggett, Lauren; Bardel, Claire; Kamsteeg, Erik‐Jan; Pfundt, Rolph; Romano, Corrado; et al.
Abstract : Objective: Cut homeodomain transcription factor CUX2 plays an important role in dendrite branching, spine development, and synapse formation in layer II to III neurons of the cerebral cortex. We identify a recurrent de novo CUX2 p.Glu590Lys as a novel genetic cause for developmental and epileptic encephalopathy (DEE). Methods: The de novo p.Glu590Lys variant was identified by whole‐exome sequencing (n = 5) or targeted gene panel (n = 4). We performed electroclinical and imaging phenotyping on all patients. Results: The cohort comprised 7 males and 2 females. Mean age at study was 13 years (0.5–21.0). Median age at seizure onset was 6 months (2 months to 9 years). Seizure types at onset were myoclonic, atypical absence with myoclonic components, and focal seizures. Epileptiform activity on electroencephalogram was seen in 8 cases: generalized polyspike‐wave (6) or multifocal discharges (2). Seizures were drug resistant in 7 or controlled with valproate (2). Six patients had a DEE: myoclonic DEE (3), Lennox‐Gastaut syndrome (2), and West syndrome (1). Two had a static encephalopathy and genetic generalized epilepsy, including absence epilepsy in 1. One infant had multifocal epilepsy. Eight had severe cognitive impairment, with autistic features in 6. The p.Glu590Lys variant affects a highly conserved glutamine residue in the CUT domain predicted to interfere with CUX2 binding to DNA targets during neuronal development. Interpretation: Patients with CUX2 p.Glu590Lys display a distinctive phenotypic spectrum, which is predominantly generalized epilepsy, with infantile‐onset myoclonic DEE at the severe end and generalized epilepsy with severe static developmental encephalopathy at the milder end of the spectrum. Ann Neurol 2018;83:926–934